2018
DOI: 10.1007/s40264-017-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Ototoxicity: Diagnosis and Monitoring

Abstract: Ototoxicity diagnosis and management has historically been approached using a variety of methods. However, in recent years a consensus on useful and practical approaches has been developed through clinical guidelines of the American Speech Language Hearing Association, the American Academy of Audiology, and multiple clinical trials published in peer-reviewed literature. Some of the guidelines and approaches are used to detect and monitor ototoxicity, while others are used to grade adverse events. Some of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 154 publications
4
41
0
4
Order By: Relevance
“…With respect to monitoring noise-induced damage to the OHCs, a common strategy for monitoring OHC function is the use of DPOAE tests. Not only are DPOAEs well known for use identifying OHC damage due to cisplatin or aminoglycoside treatments (for recent review, see Campbell and Le Prell 2018), DPOAEs have shown high sensitivity to noise injury with deficits in DPOAE amplitude reportedly associated with occupational noise (Seixas et al 2004;Korres et al 2009;Seixas et al 2012;Boger, Sampaio, and Oliveira 2017), recreational music player use (Santaolalla Montoya et al 2008;Lee et al 2014) and military service (de Souza Chelminski Barreto et al 2011). Observations that noise-induced deficits in DPOAE and click-evoked otoacoustic emission (CEOAE) thresholds significantly exceeded noise-induced TTS have been used to suggest that OAEs are a more sensitive measure of noise injury than the audiogram itself .…”
Section: Effects Of Noise On Cochlear Hair Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to monitoring noise-induced damage to the OHCs, a common strategy for monitoring OHC function is the use of DPOAE tests. Not only are DPOAEs well known for use identifying OHC damage due to cisplatin or aminoglycoside treatments (for recent review, see Campbell and Le Prell 2018), DPOAEs have shown high sensitivity to noise injury with deficits in DPOAE amplitude reportedly associated with occupational noise (Seixas et al 2004;Korres et al 2009;Seixas et al 2012;Boger, Sampaio, and Oliveira 2017), recreational music player use (Santaolalla Montoya et al 2008;Lee et al 2014) and military service (de Souza Chelminski Barreto et al 2011). Observations that noise-induced deficits in DPOAE and click-evoked otoacoustic emission (CEOAE) thresholds significantly exceeded noise-induced TTS have been used to suggest that OAEs are a more sensitive measure of noise injury than the audiogram itself .…”
Section: Effects Of Noise On Cochlear Hair Cellsmentioning
confidence: 99%
“…Exposure to loud sound has the potential to damage cells in the inner ear. It has long been known that the outer hair cells (OHCs) are particularly vulnerable to noise injury (Wang, Hirose, and Liberman 2002; for review, see Hu 2012), as well as other diverse insults such as occupational chemical exposure (for review, see Morata and Johnson 2012) and ototoxic drugs including aminoglycoside antibiotics and chemotherapeutics (for review, see Campbell and Le Prell 2018). More recently, it has become clear that the synapses connecting the inner hair cells (IHCs) to the auditory nerve dendrites are also vulnerable to loss as a consequence of noise (for review, see Kujawa and Liberman 2015), aminoglycoside antibiotics (Hinojosa and Lerner, 1987) and aging (Sergeyenko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Up until recently there has been limited research that investigates the current ototoxicity assessment and management practices in South Africa. This is a serious gap in evidence on ototoxicity monitoring, which Campbell and Le Prell [26] emphasize should cover detection and monitoring as well as grading of adverse events in any context. This is an important area for research because of the increased risk of communicable diseases that require ototoxic medication for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 A second major cause of acquired hearing loss in children and adults is treatment with lifesaving pharmaceutical agents that are toxic to the inner ear (for a review, see Campbell and Le Prell). 12 Drug-induced hearing loss (DIHL) often occurs as a side effect of treatment with lifesaving drug agents such as cisplatin and aminoglycoside antibiotics. Many of the agents that have been assessed for the prevention of NIHL also have assessed for potential prevention of DIHL, as there is significant overlap in the mechanisms of cell death that are activated by noise exposure and by ototoxic drugs.…”
Section: The Need For Otoprotective Drug Agentsmentioning
confidence: 99%